Analyzing the Accuracy and Bias in Online News Reporting During the 2022 Philippine National Elections - Jesus, Dennis A. De (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates framing bias and accuracy in online news coverage during the May 2022 Philippine general elections. Through a content analysis of 200 articles from five major outlets Rappler, ABS-CBN Online, GMA News Online, Philippine Star, and Manila Bulletin published from April 1 to May 9, 2022, the study assessed factual accuracy by cross-checking with Tsek.ph’s fact-check database and examined partisan framing toward candidates Ferdinand Marcos Jr. and Leni Robredo. Operational risk levels were evaluated using an adaptation of the Global Disinformation Index (GDI) framework, tailored to assess editorial transparency, correction policies, and ownership disclosure. Results reveal an overall accuracy rate of 82.8%, with 17.2% misreporting and 34.5% partisan framing. Statistical cross-tabulation indicates a significant correlation between editorial risk and both misinformation frequency and framing bias. Outlets with low editorial risk (e.g., Rappler, ABS-CBN) exhibited greater accuracy and balanced reporting, while those with higher risk showed more bias and misinformation. The findings highlight the importance of editorial openness and robust correction systems in safeguarding journalistic integrity during elections (Reyes & Go, 2023).